The potential for emojis to facilitate communication between patients and healthcare professionals: results from a digital survey and qualitative interviews - Essex, Margaret Noyes; Blakeman, Karin Hygge; Dietrich, Caroline E.; Arnheim-Dahlström, Lisen (Frontiers in Communication, 2024)
IntroductionEffective communication is essential for building a successful patient–healthcare professional (HCP) relationship. Understanding a patient’s emotional context is key to building this relationship. However, communication barriers often hinder the development of these relationships. Strategies to communicate emotions in healthcare settings may address this issue. Emojis are small images that together form a universal language well-suited to describe emotions.MethodsThis three-phase feasibility study used quantitative and qualitative approaches to explore current opinions around the utility of emojis in expressing emotions during patient–HCP communications. In phase 1, members of the War on Cancer digital community participated in an online survey to determine their use of emojis in personal and healthcare communications. In phase 2, selected patient volunteers were interviewed to further understand the responses from the survey. In phase 3, invited HCPs were interviewed to evaluate their use of digital communications and emojis with patients, and insights on the findings from phases 1 and 2.ResultsIn phase 1, 290 community members responded to the survey (16–84 years old; twenty-two countries). Of these, 70% (n = 197/280) reported common use of emojis in personal conversations, and 62% (n = 158/256) were optimistic about their use in HCP communications. All eight patients interviewed in phase 2 (30–70 years old; three countries) used emojis in personal communications but rarely in healthcare settings. They identified four situations where emojis could be useful in HCP communication: emotional preparation before a visit, follow-up after a visit, situations with a language barrier, and to replace numeric scales when expressing strength of emotion. All five of the HCPs interviewed in phase 3 (30–45 years old; two countries) communicated digitally with patients through electronic medical records or other platforms, but none had used emojis with patients. HCPs agreed with the four scenarios identified by patients in phase 2, further suggesting that emojis may be helpful for patients with poor literacy or difficulty expressing emotions.ConclusionIn this study, patients and HCPs agreed that emojis could potentially enhance patient–HCP communication by facilitating emotional expression. Further research is required to evaluate the practicalities and benefits of integrating emojis into healthcare communications.